Manajemen Pencegahan Tindakan Bullying di MIN 8 Aceh Barat - Sindy Aulia; Junias Zulfahmi; Ade Kurniawan (Seutia Hukamaa Cendekia, 2024)
Bullying behavior has serious repercussions for victims and perpetrators. The victim he experienced psychosomatic symptoms, went to madrasa, felt worthless, felt alienated, and depressed. As for the perpetrator, he will develop into a dangerous individual when he grows up. This article will examine how to prevent bullying in MIN 8 West Aceh. This research uses qualitative methods. The subjects of this study include the head of the madrasah, the homeroom teacher, and students at MIN 8 West Aceh. The authors used observation, interview, and documentation methods in data collection. Data analysis is used in this study to reduce and display data and draw conclusions. The results showed that the madrasah has carried out good management related to preventing bullying in the madrasah environment. The madrasah started by formulating an appropriate program plan to prevent bullying. Planning is formulated by conducting program preparation work meetings involving teacher councils and stakeholders. Then, the program that has been prepared is carried out properly by the plans that have been prepared. The program implemented is anti-bullying guidance and socialization activities through poster media. The implementation of the program is well-evaluated by the madrasah. The evaluation is carried out by evaluating processes and results.